(untitled) (Journal Nutrizione, 2025)
Stunting is a chronic nutritional problem that has a long-term impact on the quality of human resources. Although the prevalence of stunting in Indonesia shows a downward trend, the figure still exceeds the WHO threshold. One important determinant of stunting is the adequacy and quality of protein intake in early childhood. This study aims to explore parents’ understanding of animal and vegetable protein consumption and its relationship to the risk of stunting. A qualitative approach with a phenomenological method was used to capture the subjective experiences of parents with children aged 0–5 years in areas at high risk of stunting. Data were collected through semi-structured in-depth interviews and analyzed using the Colaizzi thematic technique. The results showed that parents’ understanding of the importance of protein quality, especially from animal sources, is still low. Economic factors, cultural perceptions, and low nutritional literacy are the main obstacles in providing balanced nutritious food for children. Vegetable protein tends to be the main choice because it is more affordable, although biologically less optimal. This study emphasizes the need for contextual and community-based nutritional interventions, as well as multi-sector policy support to improve community access and understanding of the importance of a combination of animal and vegetable protein in preventing stuntings